The effects of feedback timing and frequency on the acquisition of cardiopulmonary resuscitation skills of health sciences undergraduate students: A 2 x 2 factorial quasi randomized study - Akizuki, Kazunori (PLoS One, 2019)
BACKGROUND: High-quality training is required to improve the cardiopulmonary resuscitation (CPR) skills. Although it has been reported that the use of a feedback device is effective, the effects of feedback timing and frequency on CPR training have not been investigated. The aim of this study was to clarify the influence of feedback frequency and timing on the acquisition of CPR skills. METHODS: Sixty-eight undergraduates were first divided into female (n = 32) and male (n = 36) groups, and randomly assigned to one of four groups for each sex: concurrent-100%, concurrent-50%, terminal-100%, and terminal-50% feedback groups. The randomization was performed using a lottery method. This study consisted of a pre-test, practice sessions, a post-test, and a follow-up test. In the practice sessions, the participants performed six 2-minute CPR sessions in accordance with the condition assigned using mannequins and feedback devices. The post-test was conducted 24 hours after the completion of the practice sessions and the follow-up test was conducted 3 months after the completion of the practice sessions. The primary outcome of the study was the overall score at the follow-up test. RESULTS: The results of the overall score at the follow-up test for each group were 88.2 ± 9.6% for concurrent-100%, 92.2 ± 6.4% for concurrent-50%, 82.6 ± 16.4% for terminal-100%, and 85.2 ± 16.9% for terminal-50%. We did not find any statistically significant difference for the overall score at the follow-up test among the four groups (p = 0.173). The ANOVA for the test sessions revealed that there were no significant main effects of feedback timing (p = 0.135) or frequency (p = 0.765), and no significant interaction between timing and frequency (p = 0.997). CONCLUSION: The present study reveals that the use of feedback devices is an important factor for higher quality CPR training, regardless of the timing and frequency with which they are used.